Toward Supporting Maxillo-Facial Surgical Guides Positioning with Mixed Reality—A Preliminary Study - Chiara Piramide; Luca Ulrich; Pietro Piazzolla; Enrico Vezzetti (Applied Sciences, 2022)
Following an oncological resection or trauma it may be necessary to reconstruct the normal anatomical and functional mandible structures to ensure the effective and complete social reintegration of patients. In most surgical procedures, reconstruction of the mandibular shape and its occlusal relationship is performed through the free fibula flap using a surgical guide which allows the surgeon to easily identify the location and orientation of the cutting plane. In the present work, we present a Mixed Reality (MR)-based solution to support professionals in surgical guide positioning. The proposed solution, through the use of a Head-Mounted Display (HMD) such as that of the HoloLens 2, visualizes a 3D virtual model of the surgical guide, positioned over the patient’s real fibula in the correct position as identified by the medical team before the procedure. The professional wearing the HMD is then assisted in positioning the real guide over the virtual one by our solution, which is capable of tracking the real guide during the whole process and computing its distance from the final position. The assessment results highlight that Mixed Reality is an eligible technology to support surgeons, combining the usability of the device with an improvement of the accuracy in fibula flap removal surgery.